A novel NAC transcription factor mediates negative regulation of early ethylene production and ripening in tomato fruits - Li, Jiawei; Han, Junwen; Li, Tong; Chen, Daoyun; Miura, Kenji; Peres, Lazaro Eustaquio Pereira; Ezura, Hiroshi; Wang, Ning (Frontiers in Plant Science, 2025)
Timely initiation of fruit ripening is crucial for improving agricultural efficiency and shelf life. While the progression of tomato ripening and the roles of ethylene and its core transcriptional controls are well established from the breaker (BR) stage onwards, the molecular mechanisms that fine-tune the transition from fruit development to ripening remain poorly understood. In this study, we identified a previously uncharacterized NAC transcription factor (TF), Ripening Accelerator (RAR), as a key negative modulator of climacteric ripening onset. In fruit, RAR is highly expressed at the mature green (MG) stage and downregulated at BR stage, preceding the climacteric ethylene burst. Silencing RAR via RNA interference significantly accelerated fruit ripening and ethylene production prior to BR stage, especially under high light conditions. RAR directly represses ACC Synthase 2 (ACS2), a key ethylene biosynthesis gene. Although RAR can form a heterodimer with the ripening-promoting NAC TF Non-Ripening (NOR), this heterodimer exhibits weaker transcriptional activation than the NOR homodimer, indicating a repressive effect of RAR on NOR-mediated activation. Moreover, RAR expression is negatively regulated by ethylene, forming a feedback loop that modulates the timing of ripening onset. Our findings uncover a previously unrecognized regulatory checkpoint in the ripening program, where RAR probably acts as a developmental safeguard to prevent premature ripening. Targeted manipulation of RAR offers a promising strategy for fine-tuning ripening onset and improve postharvest fruit quality across diverse environmental conditions.